Inclusion and Accessibility in The Human Factors and Ergonomics Society. (December 2020) - Gomes, Kylie M.; Nguyen, Theresa; Stonewall, Jacklin; Davis, Kermit; Coppola, Sarah; Hallett, Kim; Williams, Rua M.
The Human Factors and Ergonomics Society Diversity Committee is entering its fourth year and continuing ways to improve diversity within the society as well as promote inclusive excellence within the HFE profession. Building on the annual meeting content from the committee's first two years, 2019's alternative format session on "HFE in Diversity, Inclusion and Social Justice: A Practical Primer" facilitated discussion amongst attendees about practical knowledge related to conducting diversity, inclusion, and social justice research. At the end of the session, a questionnaire was administered to gather input for future annual meeting programming. A topic of interest that emerged included promoting inclusion in HFE training, education, and the profession as a whole. Therefore, with input from past participants, this panel brings together researchers, experts, and HFES leadership to discuss challenges related to inclusion and accessibility within the society and profession, as well as how to move forward to address these challenges.